Kemampuan Komunikasi Verbal Mahasiswa PGSD dalam Menyampaikan Konsep Matematika - Mubarok, Mubarok; Yulandra , Rianty (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
Verbal communication skills are essential for students in the Primary School Teacher Education (PGSD) program, especially in delivering mathematical concepts that tend to be abstract and require clear explanations. However, initial observations revealed that many PGSD students struggle to express mathematical ideas orally, whether during discussions, presentations, or classroom interactions. This study aims to analyze the verbal communication skills of PGSD students in the context of mathematics learning. The research employed a narrative qualitative method, with data collected through participatory observation, semi-structured interviews, and documentation. The subjects were PGSD students at a public university in Indonesia who were enrolled in a Primary Mathematics Education course. The findings indicate that most students were unable to present material in a structured manner, did not adjust their communication style to the audience, and rarely allowed for two-way interaction. The study concludes that students’ verbal communication skills need to be improved through practice and structured training to prepare them to become effective and communicative primary school teachers